Physical modelling of damage mechanism of slopes containing near horizontal weak layers under rainfall conditions - Zhigang TAO; Chuang XU; Songyuan LIU; Yong LI; Kexin XIU (Meitan xuebao)
In recent years, with the continuous scale expansion of surface coal mining in China, the stability and safety of slopes in surface mining areas have received more and more attention. The slopes of the Baozhixil surface coal mine located in the Chenqi coal field are characterised by low rock strength, small inclination of strata and weak interlayers, which are prone to serious sliding damage under rainfall conditions. In order to investigate the damage mechanism of such slopes under rainfall conditions and the control effect of the NPR anchor cable support system on such slopes, model experiments and numerical simulations were used. The results show that: ① from the field damage characteristics and model test results, it can be seen that the slope damage mode is the slope shear-slip caused by weak layer belt damage under the action of rainfall. The rainfall infiltration is the main factor inducing the destruction of the slope. The damage is divided into three phases: the initial deformation, the destruction of weak layer and the overall destruction. From the results of displacement monitoring, it can be seen that the slope cracks can be up to 35 mm wide, indicating that the slope slippage damage. ② From the numerical simulation analysis, it can be seen that the slope deformation increases significantly under rainfall conditions, and the maximum deformation can be up to 40 cm without anchoring measures. At the same time, the closer to the coal seam position, the larger the area of the plastic zone of slope shear damage, and the landslide body appears to have a large area of shear damage after sliding along the weak layer of the rock body, which verifies the deformation form of slope shear-slip damage. ③ From the comparative analysis of the NPR anchor cable reinforcement scheme and the PR anchor cable reinforcement scheme, it can be seen that the supporting effect of the NPR anchor cable is much better than that of the PR anchor cable, the maximum displacement of the slope under the NPR anchor cable support is reduced by 17.6 cm, while the maximum displacement of the slope under the PR anchor cable support is reduced by only 10.3 cm. The plastic damage zone under the NPR anchor reinforcement basically disappears, while the plastic damage zone under the PR anchor reinforcement still exists and extends to the depth of the slope, and the slope has the potential of landslide. The study investigated the damage mechanism of the near-level weak layer slope under rainfall conditions, proposed the NPR anchor reinforcement scheme and verified its feasibility, which provides a certain reference basis for related slope projects.